Argumentacja hagiograficzna w tekstach maryjnych Żywotów świętych (1579) Piotra Skargi. Na przykładzie utworu O Zwiastowaniu Panny Maryjej Bogarodzice, i wcieleniu Syna Bożego - Kiszkowiak, Katarzyna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
In the light of the work O Zwiastowaniu Panny Maryjej Bogarodzice, i wcieleniu Syna Bożego Piotr Skarga emerges as an outstanding rhetorician, hagiographer, biblical scholar and theologian. In it he uses hagiographic arguments aimed at convincing the reader of the heroine’s sanctity. In order to emphasize the significance of the events he describes, Skarga makes frequent reference to The Bible, above all in the domain of inventio. In doing so, he does, of course, remain in compliance with the tenets of the Catholic faith. Because his Lives of the Saints are addressed to a wide readership, and not just to theologians, Skarga consistently avoids all theological inquiry, and is content to accept the Church’s teaching in these matters. By simplifying the problems in this way, his text gains in clarity and conciseness, thereby increasing the chances of achieving his persuasive and didactic objectives, namely, to convince the reader that the Virgin Mary is the holiest of the saints.